FLAIR Vascular Hyperintensity is a Surrogate of Collateral Flow and Leukoaraiosis in Patients With Acute Stroke Due to Proximal Artery Occlusion. Issue 2 (6th August 2015) - Karadeli, Hasan H.; Giurgiutiu, Dan‐Victor; Cloonan, Lisa; Fitzpatrick, Kaitlin; Kanakis, Allison; Ozcan, Muhammed E.; Schwamm, Lee H.; Rost, Natalia S.
ABSTRACT: BACKGROUND: Fluid attenuated inversion recovery (FLAIR) vascular hyperintensity (FVH) is a novel radiographic marker detected in acute ischemic stroke (AIS) patients, which is linked to slow blood flow and potentially salvageable brain tissue. Poor leptomeningeal collateral status in AIS patients with proximal artery occlusion (PAO) is associated with larger final infarct and worse clinical outcomes, which are also affected by severity of white matter hyperintensity (WMH). We sought to evaluate FVH utility as a marker of acute collateral vessel status and its association with WMH burden in AIS patients. METHODS: Consecutive AIS patients with PAO on baseline CT angiography (CTA) were retrospectively selected from a prospectively derived database. FVH was graded by its location, degree, and score on admission MRI obtained immediately after intravenous tissue plasminogen activator administration. Leptomeningeal collateral flow grade was ranked on admission CTA. WMH volume (WMHV) was assessed using a validated volumetric protocol. Relationship between FVH, collateral flow grade, and WMHV were analyzed. RESULTS: Among 39 patients (mean age 70.5 ± 12.7 years; 56% women, mean National Institutes of Health Stroke Scale score 17.2 (± 4.4)), median WMHV was 6.0 cm 3 . FVH score and collateral flow grade were significantly correlated (Spearman's ρ = .41, P = .009). In a univariate regression model, FVH degree was inversely associated with WMHV (β = –.33, P = .04). CONCLUSIONS: FVH score detected on acute MRI can be used as a surrogate of collateral flow grade in AIS patients. FVH degree is inversely associated with WMHV, possibly signifying diffuse disease of cerebral vasculature in patients with severe leukoaraiosis.